Study on collection and transportation of waste in Kota Samarahan - Khairul Khuzaimah, Abdul Rahim (Universiti Malaysia Sarawak, UNIMAS, 2006)
This report presents the study of the current method of collection and transportation of domestic waste in Kota Samarahan and recommendations to improve the current system. As a comparison to the former matter, the current method of collection and transportation of domestic waste in Kuching is also collected and analyzed.